Three-dimensional fate mapping of larval tissues through metamorphosis in the glass sponge Oopsacas minuta - Leys, S. P.; Kamarul Zaman, A.; Boury-Esnault, N. (Invertebrate Biology, 2016)
The tissue of glass sponges (Class Hexactinellida) is unique among metazoans in being largely syncytial, a state that arises during early embryogenesis when blastomeres fuse. In addition, hexactinellids are one of only two poriferan groups that already have clearly formed flagellated chambers as larvae. The fate of the larval chambers and of other tissues during metamorphosis is unknown. One species of hexactinellid, Oopsacas minuta, is found in submarine caves in the Mediterranean and is reproductive year round, which facilitates developmental studies; however, describing metamorphosis has been a challenge because the syncytial nature of the tissue makes it difficult to trace the fates using conventional cell tracking markers. We used three-dimensional models to map the fate of larval tissues of O. minuta through metamorphosis and provide the first detailed account of larval tissue reorganization at metamorphosis of a glass sponge larva. Larvae settle on their anterior swimming pole or on one side. The multiciliated cells that formed a belt around the larva are discarded during the first stage of metamorphosis. We found that larval flagellated chambers are retained throughout metamorphosis and become the kernels of the first pumping chambers of the juvenile sponge. As larvae of O. minuta settle, larval chambers are enlarged by syncytial tissues containing yolk inclusions. Lipid inclusions at the basal attachment site gradually became smaller during the six weeks of our study. In O. minuta, the flagellated chambers that differentiate in the larva become the post-metamorphic flagellated chambers, which corroborate the view that internalization of these chambers during embryogenesis is a process that resembles gastrulation processes in other animals.